(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
When you were reading the works of the writer Ulugbek, you remembered one aspect that made the situation worse. You can’t just read them, because every single sentence is a rebus, a whole world of thought lies behind it. In order to understand them, he comes to find the key to each sentence, to bite the core. You can’t feel the axle landing now. In order to understand the works, the reader needs to have a broad worldview, thinking, but also a simple view.